STRATEGI KOMUNIKASI PENGASUH DALAM PEMBENTUKAN AKHLAK SANTRI DI PONDOK PESANTREN DARUL TAUHID NAGARI SELAYO KABUPATEN SOLOK - Vickri Adrian Verlis; Asrul Harahap (ADISAM PUBLISHER, 2024)
The research carried out was field research using descriptive qualitative methods. Data collection techniques are carried out using techniques such as observation, interviews and documentation. Data analysis techniques use techniques in the form of data redaction (data reduction), data presentation (data display), and drawing conclusions and verification (conclusions/verification). Based on the results of the research conducted, there are various forms of communication strategies between caregivers and students in forming morals, including direct teaching, congregational Koran reading, ta'lim assemblies and group discussions. Through direct teaching, the ustadz/ustadzah provide material to their students. Congregational Koran activities such as reading the Koran guided by the teacher correct the recitation and explain its meaning. The ta'lim assembly provides in- depth lectures on religion and becomes a forum for discussion. Group discussions allow students to interact in small groups. In developing the morals of santri there are several factors, supporting factors include the existence of a budget and facilities such as buildings, prayer rooms, the Koran, and books about morals that support the activities of forming the morals of santri. Inhibiting factors include the family's minimal educational background, especially in the field of religion. Many students come from remote or remote areas who have poor basic religious knowledge, so religious formation must start from the basics